Political Approach In Islamic Studies - Sayyidaturrohimah; Mubaraq, Zulfi; Syuhadak; Taufiqurrochman (Al-Ubudiyah: Jurnal Pendidikan dan Studi Islam, 2023)
This research aims to to know and understand the meaning of etymology, terminology and characteristics or concrete manifestations of the political approach in Islamic studies, to understand and find out what are the factors that cause the existence of this political approach so that it is used in studying Islamic studies, and to find out and understand what are the academic implications that arise from using this political approach in understanding Islamic studies. This article is written based on the type of literature research with primary data in the form of 30 main references which are divided into 3 material objects to be studied. The research results show that: 1) As a method used in studying Islam in depth, the political approach is always related to the benefit of the people and humans. This shows that politics is not always negative. 2) The existence of a political approach is influenced by several factors. The existence of similarities in the object of study makes Islam deepen through this method. However, it cannot be denied that the differences in the views of the ulama' on the relationship between Islam and politics are also a factor that hinders its existence. 3) A political approach can have a positive impact in the form of several leadership and government lessons that can be applied from the time of the Prophet to his successors caliphs. The existence of a field of Islamic science that specifically discusses government can also be useful for a leader of the people.